Ugetismo y socialismo en la España rural : Teba, un siglo de historia / Manuel Morales Muǫs (ed.) - Morales Muǫz, ManuelSalguero Espárraga, Salvador (1914-1994)
Contiene Memorias de Salvador Salguero Espárraga